Comparative study of clan CA cysteine proteases: an insight into the protozoan parasites - Moyo, Sipho Dugunye (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Protozoan infections such as Malaria, Leishmaniasis, Toxoplasmosis, Chaga's disease and African trypanosomiasis caused by the Plasmodium, Leishmania, Toxoplasma and Trypanosoma genuses respectively; inflict a huge economic, health and social impact in endemic regions particularly tropical and sub-tropical regions. The combined infections are estimated at over a billion annually and approximately 1.1 million deaths annually. The global burden of the protozoan infections is worsened by the increased drug resistance, toxicity and the relatively high cost of treatment and prophylaxis. Therefore there has been a high demand for new drugs and drug targets that play a role in parasite virulence. Cysteine proteases have been validated as viable drug targets due to their role in the infectivity stage of the parasites within the human host. There is a variety of cysteine proteases hence they are subdivided into families and in this study we focus on the clan CA, papain family C1 proteases. The current inhibitors for the protozoan cysteine proteases lack selectivity and specificity which contributes to drug toxicity. Therefore there is a need to identify the differences and similarities between the host, vector and protozoan proteases. This study uses a variety of bioinformatics tools to assess these differences and similarities. The Plasmodium cysteine protease FP-2 is the most characterized protease hence it was used as a reference to all the other proteases and its homologs were retrieved, aligned and the evolutionary relationships established. The homologs were also analysed for common motifs and the physicochemical properties determined which were validated using the Kruskal-Wallis test. These analyses revealed that the host and vector cathepsins share similar properties while the parasite cathepsins differ. At sub-site level sub-site 2 showed greater variations suggesting diverse ligand specificity within the proteases, a revelation that is vital in the design of antiprotozoan inhibitors.
Keywords: Cysteine proteinases; Proteolytic enzymes; Protozoan diseases; Parasites; Protozoan diseases -- Chemotherapy; Bioinformatics; Plasmodium; Antiprotozoal agents